2002
DOI: 10.1097/00008571-200203000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Tolbutamide is known to be metabolized by cytochrome P450 2C9 (CYP2C9), and the effects of the CYP2C9 amino acid polymorphisms *2 (Arg144Cys) and *3 (Ile359Leu) could be important for drug treatment with tolbutamide and for use of tolbutamide as a CYP2C9 test drug. Tolbutamide pharmacokinetics and plasma insulin and glucose concentrations were studied in 23 healthy volunteers with all six combinations of the CYP2C9 alleles *1, *2 and *3, including two subjects with the combined CYP2C9*1/*1 and CYP2C19*2/*2 gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(24 citation statements)
references
References 26 publications
1
22
0
1
Order By: Relevance
“…However, they are mostly based on either in-vitro results, clinical studies with small healthy cohorts and/or heterogeneous cohorts of patients without consideration of concomitant medication, or meta analyses of these studies [4,16,17]. Only few data are available for cohorts where both typing procedures have been used on the same healthy persons, and there is a lack of statistical analysis of phenotypes to determine confidence limits for any estimated parameters [18]. Here, we provide this type of information for CYP2C9 activity by combining genotyping with phenotyping for a cohort of 283 healthy students, using FLB as probe drug.…”
Section: Introductionmentioning
confidence: 99%
“…However, they are mostly based on either in-vitro results, clinical studies with small healthy cohorts and/or heterogeneous cohorts of patients without consideration of concomitant medication, or meta analyses of these studies [4,16,17]. Only few data are available for cohorts where both typing procedures have been used on the same healthy persons, and there is a lack of statistical analysis of phenotypes to determine confidence limits for any estimated parameters [18]. Here, we provide this type of information for CYP2C9 activity by combining genotyping with phenotyping for a cohort of 283 healthy students, using FLB as probe drug.…”
Section: Introductionmentioning
confidence: 99%
“…Celecoxib. CYP2C9*3 has been associated with reduced celecoxib metabolism in vitro and in five of six in vivo studies (Kirchheiner et al, 2003e;Tang et al, 2001;Werner et al, 2002;Stempak et al, 2005;Lundblad et al, 2006). Individuals heterozygous and homozygous for CYP2C9*3 had 1.5-and 3.0-fold higher AUCs in one single-dose study (Kirchheiner et al, 2003e).…”
Section: B Cyp2c9mentioning
confidence: 96%
“…CYP2C9*3 has been associated with reduced celecoxib metabolism in vitro and in five of six in vivo studies (Kirchheiner et al, 2003e;Tang et al, 2001;Werner et al, 2002;Stempak et al, 2005;Lundblad et al, 2006). Individuals heterozygous and homozygous for CYP2C9*3 had 1.5-and 3.0-fold higher AUCs in one single-dose study (Kirchheiner et al, 2003e). An earlier single-dose study reported that the three highest AUC values (ϳ2 times the mean AUC of all participants) were seen in carriers of *3 alleles (Tang et al, 2001), whereas another study reported that a PM had a 2-fold higher AUC than the mean of 11 EMs (genotyping was undertaken but only the predicted phenotype was reported) .…”
Section: B Cyp2c9mentioning
confidence: 96%
See 1 more Smart Citation
“…Similarly, CYP2C9*3/*3 genotype has a greater impact on the kinetics of antidiabetic agents, such as glyburide and tolbutamide, compared to CYP2C9*2/*2 genotype [113,114]. The oral clearance value of glyburide was 54.3 ml/min in volunteers with CYP2C9*1/*1 genotype, 48.3 ml/min in those with CYP2C9*2/*2 genotype, and 11.2 ml/min in subjects with CYP2C9*3/*3 genotype.…”
Section: Cyp 2c9mentioning
confidence: 99%